EDUCATIONAL TOOLS FOR SOCIAL INTEGRATION OF INTERNALLY DISPLACED PERSONS: INTERNATIONAL DIMENSION - OLIINYK, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines international experience in using educational tools for the social integration of internally displaced persons. As of December 2024, there were 3,665,000 internally displaced persons in Ukraine. One of the main problems of internally displaced persons in Ukraine is their social integration. After moving to other regions of the country, IDPs face various difficulties, such as lack of housing, problems with employment and adaptation to new conditions. They often experience social isolation and have limited access to educational, medical and social services. One of the most powerful tools for solving their adaptation problems is education, which not only allows IDPs to acquire new skills, knowledge and abilities, but also contributes to their socialization and development as active members of society. Educational programs help overcome cultural barriers, contribute to the development of civic consciousness, and provide employment opportunities and stability at the social and economic levels. The study was conducted based on an analysis of the experience of countries for which the problem of forced internal migration has been and remains extremely relevant: Georgia, Somalia, Ethiopia, Armenia and Iraq. It was found that educational initiatives for IDPs in different countries of the world demonstrate various approaches to social integration and include language training, vocational training and skills development, education of IDP children, and development of personal skills. In order to increase the effectiveness of educational programs, countries should develop national mechanisms for financing educational initiatives, ensure equal access to educational opportunities for all IDPs, simplify bureaucratic procedures and create favorable conditions for the training and employment of IDPs. The application of world experience in Ukraine will allow developing more effective educational strategies to support IDPs, taking into account the challenges associated with war and mass population displacement.